Self Management and Learning Interests on Nursing Students Level III of STIKes Santa Elisabeth Medan - Barus, Mardiati; Rupang , Ernita Rante; Miltri Januarti Munthe (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
The declining academic quality has been attributed to a waning interest in learning. To address this, effective self-management strategies are crucial. Self-management involves organizing tasks, managing time, making choices, pursuing interests, and preparing mentally and physically. This study examined the relationship between students' self-management abilities and learning preferences in the Level III Nursing program at STIKES Santa Elisabeth Medan in 2023. The study used descriptive analysis with a cross-sectional approach and employed univariate and bivariate analyses, including the Chi-Square test. Results showed that 78.7% of students demonstrated good self-management abilities, while 62.8% displayed an interest in learning. The Chi-Square test indicated no significant relationship (p = 0.816) between students' autonomy and their learning interest in the Level III nursing program at STIKES Santa Elisabeth Medan. In conclusion, the research findings indicate no significant correlation between self-management and learning interests among Santa Elisabeth Medan Ners STIKES students in 2023.